Stabilizing Business Cycles by PLS Banking and Ethic Economics - Bidabad, Bijan (International Journal of Shari’ah and Corporate Governance Research, 2019)
In addition to discuss economic cycle’s theories in this paper by decomposing money market into two markets of "saving-depositing" and "investment-credit facilities", we study the time structure behavior of depositor-bank-investor and conclude that the traditional banking structure creates fluctuations in money sector and interest rate. These fluctuations affect the real sector through saving and investment and undulate the economy as well. Mathematical derivations show that banking structure is one of the main factors of economic cycles. Therefore, the abolition of usury (Riba) is proposed as the solution to relate directly investment to saving via The Rastin Profit and Loss Sharing Banking. In this framework, the bank offers investment management services and obtains commission. In The Rastin Profit and Loss Sharing Banking risks are practically transferred from credit facility sector (loans) to deposit sector and bank does not face any losses. On the other hand, the creation of a strong structural relationship between the interest rate of deposits and credit facility interest rate does not let any losses to occur in the capital market while there is profit in the deposit market. This concept is against the conventional banking system in which if the borrower obtains profit or loss; he has to pay interest (profit) to the depositor.The second pathological defect of economic crisis is the excessive consumption and economic greed and similar bad habits which expand economic cycles. The adjustment of mankind behavior, according to Islamic and other divine religions ethical and mystical tuitions, will practically prevent the intensity of crises. Prevention of extravagance frees a large portion of economic resources, and therefore, the magnitude of the business cycle will be reduced, and economic stability will be relatively increased.